EFEKTIVITAS PENERAPAN STRATEGI INSIDE OUTSIDE CIRCLE UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB MELALUI MUHADATSAH - muhammad ridwanullah fauzi, - (2020)
This research is based on the problems experienced by students at the Daaarul Uluum Lido Modern Islamic Boarding School in improving Arabic speaking skills. Muhadatsah learning is carried out as an activity in improving the ability to speak Arabic seem monotonous and without vareasi. So that students' speaking abilities are only limited. As well as being considered less extensive in exporting in terms of Arabic. In this situation the development of students' speaking skills will only reach the point where the child merely completes the activities of Muhadatsah as an obligation. From this the authors took the initiative to provide a new strategy treatment that is the Inside Outside Circle Strategy as a new learning in improving students' Arabic speaking ability through learning Muhadatsah. Data collection techniques used were, observation, tests, and interviews. Based on the results of research into the application of the Inside Outside Circle learning strategy it is known that the use of this strategy is quite capable of increasing students' interest and ability in learning Muhadatsah. Learning by applying this is very helpful for teachers in carrying out Muhadatsah activities. Because learning using this strategy is very effective because it does not become a monotonous activity but it becomes a cheerful activity. On this basis this strategy is sufficient to be recommended and makes a clear reference in language learning. Keyword : Muhadatsah, Inside Outside Circle, Arabic Languange